(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to investigate the moderating mediation effect of lifelong education on the mediation effect of hope on suicide ideation in the elderly. The subjects of this study were 280 elderly people living in S city of Chungnam-do, Korea. Method/Statistical analysis: The collected data are analyzed using correlation analysis, frequency analysis, and moderating mediation effect. Findings: First, the correlation analysis showed a positive correlation between quality of life and hope, but there was a positive correlation between quality of life and suicide ideation, hope and suicide ideation. Second, the hope of the elderly mediated the relationship between the quality of life and suicide ideation. Third, participation in lifelong education of the elderly moderated the relationship between quality of life and hope. Fourth, participation in lifelong education of elderly people moderated the mediating relationship of hope between quality of life and suicide ideation. Improvements/Applications: Finally, based on the results of this study, it was suggested that a lifelong education program should be developed to lower the suicide intention of the elderly. In addition, we discussed regional comparisons through nationwide sampling, research on various age groups, and directions for research targeting only vulnerable groups.